2021
DOI: 10.1093/nar/gkab1200
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of network-based integration from multi-omics longitudinal data

Abstract: Multi-omics integration is key to fully understand complex biological processes in an holistic manner. Furthermore, multi-omics combined with new longitudinal experimental design can unreveal dynamic relationships between omics layers and identify key players or interactions in system development or complex phenotypes. However, integration methods have to address various experimental designs and do not guarantee interpretable biological results. The new challenge of multi-omics integration is to solve interpre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Integration of a PPI network in a multi-omics context is nowadays an essential issue in the understanding of biological mechanisms ( Hawe, Theis and Heinig, 2019 ; Bodein et al, 2021 ; Dimitrakopoulos et al, 2021 ). To integrate an interaction into a network, it must first be estimated by a so-called confidence score ( Stelzl and Wanker, 2006 ; Li et al, 2016 ; Xu et al, 2021 ), representing probability that the interaction is accurately identified by algorithms and is expressed as a percentage ( Kamburov et al, 2012 ; Peng et al, 2017 ).…”
Section: Methods Based On Text Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of a PPI network in a multi-omics context is nowadays an essential issue in the understanding of biological mechanisms ( Hawe, Theis and Heinig, 2019 ; Bodein et al, 2021 ; Dimitrakopoulos et al, 2021 ). To integrate an interaction into a network, it must first be estimated by a so-called confidence score ( Stelzl and Wanker, 2006 ; Li et al, 2016 ; Xu et al, 2021 ), representing probability that the interaction is accurately identified by algorithms and is expressed as a percentage ( Kamburov et al, 2012 ; Peng et al, 2017 ).…”
Section: Methods Based On Text Miningmentioning
confidence: 99%
“…However, in a multi-omics integrations context one seeks above all to connect information from different omics fields (transcriptomics, proteomics, metabolomics, lipidomics, and metabolomics ( Haas et al, 2017 ; Fan, Zhou and Ressom, 2020 ; Cansu Demirel, Kaan Arici and Tuncbag, 2022 ). In this context, multi-layer algorithms for visualization are preferable to force-directed algorithms ( Bodein et al, 2021 ; Dursun, Kwitek and Bozdag, 2021 ; Marín-Llaó et al, 2021 ). There are several algorithms for implementing multi-layer networks, in the context of multi-omics integration, the most highlighted implementation is the one named by Hammoud and Kramer, (2020) : “Interactive/Interconnected/Interdependent Networks and Networks of Networks Implementation.” This implementation has as input a set of monoplex networks (single layer networks, e.g., PPI network).…”
Section: Methods Based On Text Miningmentioning
confidence: 99%
“…Mapping environment-to-phenotype has already been shown as an effective theoretical approach to study population adaptation strategies ( Xue et al., 2019 ), new frameworks to model complex gene-environment interaction show promise for more accurate disease risk estimation ( Li et al., 2019a ), and advanced approaches to integrate multimodal ( Pan et al., 2022 ) and longitudinal multi-omics are emerging ( Bodein et al., 2021 ; Kaur et al., 2020 ; Li et al., 2020 ). However, extending functional exposomics models to complex organisms and societies entails challenges, including i) the difficulty to incorporate measures of psychosocial and perceived factors alongside biological and physical factors, ii) the complexity to integrate individualized molecular measures with community-level data, iii) the fusion of exposure, response, and effect measures in interpretable dynamic networks and most critically, iv) the translation of knowledge to operable practices that improve wellbeing.…”
Section: Functional Exposomics: Concept To Applicationmentioning
confidence: 99%
“…Methods can be co-expression based, topology based, pan-sample based and multi-edge based including tools such as WGCNA, SimMod, ModulOmics, and LemonTree [31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%